Comparison of meat yield and quality characteristics between indigenous chicken and commercial broiler (Bangladesh Veterinarian, 2018)
Yield and quality of meats from commercial broiler and indigenous chickens weighing one kg each were studied during different periods of refrigeration. The chicken carcasses were stored at -20oC for 30 days and were analyzed on 0, 15 and 30 days. Carcass weight (%), shank weight (%), dressing (%), breast meat yield (%) were higher (P